(3OjhGf GdVhHQjs - (3CHhHcQ CMeO Hf eMeO Hf GdMSf Hf eQGQ GdVHj GdMdHj GdVhHQj,J (B334 (3g` s
(3ChdgG (B:s
(3bGd CHhHcQ GdVhHQj aj gOjI TeY CgOGgG(B: (3jG CHG MaU bO CNJQJ ade Bd ENjJGQG s
(3BNQgG (B:s
(3hbGd jQKj CHfJg(B: (3ef dbdhH MQbg ef dYjhf CQbg s
(3ocJHJ HQSe NRGfI Gdedi CejQ Gdedc TeS GdOjf CHj GdeYGdj GdghGQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B198s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B145 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLeYjI GdBSjhjI HcdcJG (B(202) s
Keywords: (3GdCOHs